Extinction and the U.S. Endangered Species Act - Noah Greenwald; Kieran F. Suckling; Brett Hartl; Loyal A. Mehrhoff (PeerJ, 2019)
The U.S. Endangered Species Act is one of the strongest laws of any nation for preventing species extinction, but quantifying the Act’s effectiveness has proven difficult. To provide one measure of effectiveness, we identified listed species that have gone extinct and used previously developed methods to update an estimate of the number of species extinctions prevented by the Act. To date, only four species have been confirmed extinct with another 22 possibly extinct following protection. Another 71 listed species are extinct or possibly extinct, but were last seen before protections were enacted, meaning the Act’s protections never had the opportunity to save these species. In contrast, a total of 39 species have been fully recovered, including 23 in the last 10 years. We estimate the Endangered Species Act has prevented the extinction of roughly 291 species since passage in 1973, and has to date saved more than 99% of species under its protection.